2014
DOI: 10.1039/c4cc00576g
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer-featured materials—promising hosts for fabrication of efficient OLEDs through triplet harvesting via triplet fusion

Abstract: A charge-transfer-featured naphthalimide derivative with a small exchange energy but a lower lying (3)ππ* state than (3)CT state is found to contribute to triplet harvesting through a P-type rather than an E-type delayed fluorescence, and could act as a quite promising host to achieve highly efficient OLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…In the solid film state, where CzPhONI molecules are tightly packed, the interactions become stronger, leading to the more bathochromic spectrum with an emission peak at $493 nm. More detailed investigations have shown that CzPhONI exhibits a twisted intramolecular CT character, and it has been reported elsewhere [16]. The density functional theory calculations show that the overlap between HOMO and LUMO is zero.…”
Section: Pl Emission Property Of Czphoni and Energy Transfer Between mentioning
confidence: 89%
See 3 more Smart Citations
“…In the solid film state, where CzPhONI molecules are tightly packed, the interactions become stronger, leading to the more bathochromic spectrum with an emission peak at $493 nm. More detailed investigations have shown that CzPhONI exhibits a twisted intramolecular CT character, and it has been reported elsewhere [16]. The density functional theory calculations show that the overlap between HOMO and LUMO is zero.…”
Section: Pl Emission Property Of Czphoni and Energy Transfer Between mentioning
confidence: 89%
“…It has been demonstrated that CzPhONI is a triplet-fusion delayed fluorescence (TFDF) material, which is related to a triplet up-conversion mechanism [16]. The up-conversion mechanism originates from the triplet-triplet annihilation (TTA) process, and the value of g r is higher than the maximum value in conventional fluorescent OLEDs [24][25][26].…”
Section: El Emission Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…When under a forward bias, holes and electrons are injected from corresponding electrodes, and excitons will be formed in CzPhONI layer for emission. Although the EL emission takes advantage of the triplet-triplet annihilation (TTA) up-conversion mechanism of CzPhONI emitter, 22 the TTA process is not as efficient as the reverse intersystem crossing (RISC) of thermally activated delayed fluorescence (TADF) materials. 23 Herein, we demonstrate a high performance organic UVPD with high EL yields.…”
mentioning
confidence: 99%